Islamic Political Communication System Mapping Millennial Muslim Geopolitics on Social Media in Facing the 2024 Presidential Election - Hasan Sazali; Mardhiah Rubani; Ismandianto Ismandianto; Misrah Misrah; Charles Julian Santos Navarro (Universitas Negeri Medan, 2023)
In political preferences, religion plays a vital role as a consideration for the millennial generation. This is because Indonesia still considers religion in setting policies as it does in political parties and general elections. This study analyzes the political communication system of millennial Muslim Islam on social media in the face of the 2024 presidential election (netnographic analysis). This study applies the netnographic research method through a qualitative approach to understand how the Islamic political communication system works in millennial Muslim society on social media and the geopolitics of millennial Muslims in Indonesia in the face of the 2024 presidential election. Data collection uses analytics related to election data—President in 2024. The study results show that the application of political communication among millennial Muslims on social media is in the form of support and criticism on the hashtag #pemilu2024. Social media proves that distance and time limits are not obstacles to voicing opinions, criticizing and supporting each other. Several things that can be done to map Islamic political communication systems and millennial Muslim geopolitics on social media include: (1) Analyze Islamic political trends that occur on social media, such as Twitter, Facebook, and Instagram, by searching for keywords related to Islamic politics and monitor how communication patterns are between Muslim millennials; (2) Understanding millennial Muslim sentiments on social media by reading and monitoring conversations on social media; and (3) understand the patterns used in communicating, taking into account the type of content they share, the frequency of social media use, as well as the most used platforms. Too much social media reach without knowing boundaries makes social media challenging to control. The strength of political competition becoming increasingly evident must be accompanied by carefulness in filtering information not to complicate the situation. As millennials amid vulnerable hostilities, they should be able to become pioneers or fortresses in avoiding the opposing currents of the impact of social media in political times.Keywords: Political Communication, Millennial Muslims, Geopolitical Mapping, Social Media, Presidential Election